WRITING FOR ACADEMIC COMMUNICATION: WHAT IS FOCUS? - Irina B. Korotkina (Moscow Polytechnic University, 2016)
The article describes one of the most challenging aspects of academic writing, or rhetoric and composition, the focus. Special attention is paid to narrowing down the topic of an academic text, formulating a clear thesis statement and the development of the main idea throughout the text. An academic text is viewed as an intellectual procedure, which enables the writer to construct new knowledge and successfully communicate it to the academic community. The paper is aimed at helping Russian students and researchers better understand the requirements of Western universities and international academic journals to theses and publications. Recommendations are based on the WAC approach, although the examples are drawn mainly from social sciences and humanities.